Advances in Huntington Disease Drug Discovery: Novel Approaches to Model Disease Phenotypes. (February 2014) - Bard, Jonathan; Wall, Michael D.; Lazari, Ovadia; Arjomand, Jamshid; Munoz-Sanjuan, Ignacio
Huntington disease is a monogenic, autosomal dominant, progressive neurodegenerative disorder caused by a trinucleotide CAG repeat expansion in exon 1 of the huntingtin ( HTT ) gene; age of onset of clinical symptoms inversely correlates with expanded CAG repeat length. HD leads to extensive degeneration of the basal ganglia, hypothalamic nuclei, and selected cortical areas, and a wide range of molecular mechanisms have been implicated in disease pathology in animal or cellular models expressing mutated HTT (mHTT) proteins, either full-length or amino-terminal fragments. However, HD cellular models that recapitulate the slow progression of the disease have not been available due to the toxicity of overexpressed exogenous mHTT or to limitations with using primary cells for long-term studies. Most investigations of the effects of mHTT relied on cytotoxicity or aggregation end points in heterologous systems or in primary embryonic neuroglial cultures derived from HD mouse models. More innovative approaches are currently under active investigation, including screening using electrophysiological endpoints, as well as the recent use of primary blood mononuclear cells and of human embryonic stem cells derived from a variety of HD research participants. Here we describe how these cellular systems are being used to investigate HD biology as well as to identify mechanisms with therapeutic potential.